Synthesis of a Trichoderma chitinase which affects the Sclerotium rolfsii and Rhizoctonia solani cell walls - Lima, L H; De Marco, J L; Ulhoa, C J; Felix, C R (Folia microbiologica, 1999)
A Trichoderma sp. isolate, hereafter called T6, produces a 46-kDa endochitinase (CHIT 46) which had been shown to drastically affect in vitro the cell walls of the phytopathogens Sclerotium rolfsii and Rhizoctonia solani. We attempted to gain insight into its properties. The CHIT 46 N-terminal amino acid sequence shares a very high homology with other fungal chitinases. Western blot analysis using polyclonal antibodies anti-CHIT 46 revealed that this enzyme is immunologically distinct from other proteins produced by the same Trichoderma isolate T6, but is immunologically identical with proteins having equivalent molar mass, probably chitinases, produced by other Trichoderma spp. isolates. In addition, the antibodies revealed also that a substantial amount of this enzyme is secreted into the culture medium 2 d after the Trichoderma isolate T6 comes into contact with chitin.
Keywords: western blotting; Sequence Homology; Rhizoctonia; myši; elektroforéza v polyakrylamidovém gelu; Blotting, Western; Fungal Proteins; Trichoderma; Animals; buněčná stěna; Electrophoresis, Polyacrylamide Gel; Cell Wall; Mice; fungální proteiny; Chitinases; chitinasy; zvířata; sekvenční homologie